952 Compare Japanese mortality due to external causes in 1984 to 2014. (1st September 2016) - Ishii, Hiroko; Uchiyama, Yuko; Tanaka, Tetsuro; Tanaka, Michio; Ikemi, Yoshiaki
Abstract : Background: The purpose of this study is to compare mortality due to external causes in Japan and to explore strategies for injury prevention. Methods: Mortality caused by external causes provided by the Vital Statistics of Japan and the standard population data were used. Results: Among 0–14 year olds, mortality due to external causes declined from 13.1 per 100, 000 population in 1984 to 3.6 in 2014. Of the types of external causes, suicide death rate increased, but drowning, motor vehicle crashes and suffocation death rate were reduced. Among 15–14 year olds, mortality due to external causes declined from 36.8 per 100, 000 population in 1984 to 26.2 in 2014. Of the types of external causes, suicide death rate increased, but drowning and motor vehicle crashes death rate were reduced. Among 45–64 year olds, mortality due to external causes declined from 63.6 per 100, 000 population in 1984 to 42.1 in 2014. Of the types of external causes, suffocation death rate increased, but motor vehicle crashes and suicide death rate were reduced. Among those 65 years or older, mortality due to external causes declined from 135.2 per 100, 000 population in 1984 to 105.1 in 2014. Of the types of external causes, suffocation and drowning death rate increased, but suicide, motor vehicle crashes and fall death rate were reduced. Conclusions: In Japan, the motor vehicle crashes death rate among all ages decreased significantly. The drowning and suffocation death rate among children decreased, but among those 65 years or older those rates increased. Laws requiring seat belts from 1985 and child seat under 6 year old from 2000 have prevented many traffic fatalities. Development of such legal systems would be useful for a decline of the death rate mortality due to external causes.